2019
DOI: 10.1186/s13063-019-3951-x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of Pre-Operative PD1 checkpoint blockade and receptor activator of NFkB ligand (RANKL) inhibition in non-small cell lung cancer (NSCLC): study protocol for a multicentre, open-label, phase 1B/2, translational trial (POPCORN)

Abstract: BackgroundNeoadjuvant immunotherapy targeting immune checkpoint programmed death-1 (PD-1) is under investigation in various tumour settings including non-small-cell lung cancer (NSCLC). Preclinical models demonstrate the superior power of the immunotherapy provided in a neoadjuvant (pre-operative) compared with an adjuvant (post-operative) setting to eradicate metastatic disease and induce long-lasting antigen-specific immunity. Novel effective immunotherapy combinations are widely sought in the oncology field… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…[55][56][57][58][59] Two trials are assessing novel immunotherapy combinations in stage I-IIIA NSCLC patients (combining anti-PD1 with anti-Lag3 or anti-RANKL). 60 61 Three studies are assessing neoadjuvant chemoimmunotherapy in stage III NSCLC patients, and these all include adjuvant ICI treatment postsurgery. [62][63][64] Finally, two trials are assessing a potential role for neoadjuvant immunoradiotherapy in patients with stage III NSCLC, with one of these involving neoadjuvant chemoimmunoradiotherapy and adjuvant ICI.…”
Section: Right Drugs? Experimental Strategies In Lung Cancer Naicimentioning
confidence: 99%
“…[55][56][57][58][59] Two trials are assessing novel immunotherapy combinations in stage I-IIIA NSCLC patients (combining anti-PD1 with anti-Lag3 or anti-RANKL). 60 61 Three studies are assessing neoadjuvant chemoimmunotherapy in stage III NSCLC patients, and these all include adjuvant ICI treatment postsurgery. [62][63][64] Finally, two trials are assessing a potential role for neoadjuvant immunoradiotherapy in patients with stage III NSCLC, with one of these involving neoadjuvant chemoimmunoradiotherapy and adjuvant ICI.…”
Section: Right Drugs? Experimental Strategies In Lung Cancer Naicimentioning
confidence: 99%
“…Some immunotherapies have been utilized to leverage the immune system to fight tumors ( Kobold et al, 2018 ; Popovic et al, 2018 ). Immune checkpoint inhibitors (ICIs), such as anti-PD-1/PD-L1, have emerged as an effective therapeutic selection for advanced breast cancer, metastatic melanoma and NSCLC ( Wang et al, 2018 ; Ahern et al, 2019 ; Liu D. et al, 2019 ). NSCLC is characterized by several mutations in the immune system, making it possible that these patients may benefit from immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the RANK/RANKL/OPG system has been observed to play a key role in tumor cell migration and invasion [7][8][9]. Studies have shown that TNFRSF11(RANK) is expressed in a variety of tumor tissues, such as osteosarcoma [10,11], chondrosarcoma [12], breast cancer [13], prostate cancer [14,15], renal cancer [16], oral squamous cell carcinoma [17], lung cancer [18], thyroid cancer [19], and melanoma [20]. However, the expression of TNFRSF11 in gastric cancer cells is rarely reported, and there is no report on the relationship between TNFRSF11 gene polymorphism and gastric cancer.…”
Section: Introductionmentioning
confidence: 99%